Modeling how iso-caloric macronutrient substitutions are longitudinally associated with plasma kynurenines in colorectal cancer survivors up to 12 months post-treatment - Holthuijsen, Daniëlle; van Roekel, Eline H.; Bours, Martijn J. L.; Ueland, Per M.; Breukink, Stéphanie O.; Janssen-Heijnen, Maryska L. G.; Konsten, Joop L.; Keulen, Eric T. P.; McCann, Adrian; Brezina, Stefanie; Gigić, Biljana; Kok, Dieuwertje E.; et al. (The journal of nutritional biochemistry, 2025)
Dietary intake of several macronutrients is associated with plasma kynurenines after colorectal cancer (CRC), and kynurenines have been linked to health-related outcomes. It is unknown how macronutrient substitution affects plasma kynurenines, which may be relevant for developing guidelines to improve post-CRC quality of life through dietary changes. Using iso-caloric substitution models, we investigated how substituting one macronutrient with another is longitudinally associated with plasma tryptophan, kynurenines, and kynurenine ratios in CRC survivors. Measurements were performed at 6-weeks, 6-months, and 12-months post-treatment in 247 stage I-III CRC survivors. Macronutrient intake was measured by 7-d dietary records and plasma kynurenines by LC/MS-MS. For analysis, we applied linear mixed models with false discovery rate (FDR) to adjust for multiple testing. After FDR adjustment, substituting 100 kcal/d of total carbohydrates with 100 kcal/d of total protein was associated with higher plasma concentrations of kynurenic acid (KA), xanthurenic acid (XA), and a higher kynurenic acid-to-quinolinic acid (KA/QA) ratio. Substituting 100 kcal/d of total carbohydrates with 100 kcal/d of total fat was associated with higher tryptophan concentrations, higher KA/QA ratio, and a lower kynurenine-to-tryptophan ratio (KTR) and hydroxykynurenine ratio (HKr). Substituting 100 kcal/d of total fat with 100 kcal/d of total protein was associated with higher XA concentrations. Altogether, iso-caloric macronutrient substitutions, particularly substituting carbohydrates with protein or fat, were longitudinally associated with higher concentrations of potentially favourable kynurenines and ratios (i.e., KA, XA, and KA/QA ratio) and lower ratios with pro-inflammatory or neurotoxic properties (i.e., KTR and HKr) in CRC survivors up to 12-months post-treatment.
Gesehen am 20.10.2025